Sclerostin Antibody Therapy for the Treatment of Osteoporosis: Clinical Prospects and Challenges - Claire MacNabb; D. Patton; J. S. Hayes (Journal of Osteoporosis)
It is estimated that over 200 million adults worldwide have osteoporosis, a disease that has increasing socioeconomic impact reflected by unsustainable costs associated with disability, fracture management, hospital stays, and treatment. Existing therapeutic treatments for osteoporosis are associated with a variety of issues relating to use, clinical predictability, and health risks. Consequently, additional novel therapeutic targets are increasingly sought. A promising therapeutic candidate is sclerostin, a Wnt pathway antagonist and, as such, a negative regulator of bone formation. Sclerostin antibody treatment has demonstrated efficacy and superiority compared to other anabolic treatments for increasing bone formation in both preclinical and clinical settings. Accordingly, it has been suggested that sclerostin antibody treatment is set to achieve market approval by 2017 and aggressively compete as the gold standard for osteoporotic treatment by 2021. In anticipation of phase III trial results which may potentially signify a significant step in achieving market approval here, we review the preclinical and clinical emergence of sclerostin antibody therapies for both osteoporosis and alternative applications. Potential clinical challenges are also explored as well as ongoing developments that may impact on the eventual clinical application of sclerostin antibodies as an effective treatment of osteoporosis.